2014
DOI: 10.1097/lgt.0b013e3182901ef3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Management of Young Women With Cervical Intraepithelial Neoplasia 2 With a 6-Month Observation Protocol

Abstract: On the basis of these data, follow-up in this population was unpredictable based on basic demographic or clinical factors that we often use to judge likelihood of compliance with medical recommendations. The percentage of patients with regression at follow-up was as expected from the natural history of CIN 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…To our knowledge, this is the first study to compare regression rates between women with CIN2 versus CIN3 managed conservatively, and it is one of the largest cohorts published regarding outcomes of conservative management of CIN2 in young women. Importantly, in terms of the primary outcome, it confirms previously published high regression rates in this age group for those with CIN2 7 , 8 , 10 , 11 , 15 , 16 with a median time to regression of 10.8 months. In addition, we have documented a regression rate of 21.6% for women with CIN3, median not reached.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…To our knowledge, this is the first study to compare regression rates between women with CIN2 versus CIN3 managed conservatively, and it is one of the largest cohorts published regarding outcomes of conservative management of CIN2 in young women. Importantly, in terms of the primary outcome, it confirms previously published high regression rates in this age group for those with CIN2 7 , 8 , 10 , 11 , 15 , 16 with a median time to regression of 10.8 months. In addition, we have documented a regression rate of 21.6% for women with CIN3, median not reached.…”
Section: Discussionsupporting
confidence: 86%
“… 1 Reasons for this include low incidence of cervical cancer, 1 5 high rate of false-positive screening tests, 6 and spontaneous resolution of precancerous lesions. 7 16 An increasing number of studies have demonstrated a high rate of regression of high grade squamous intraepithelial lesion (HSIL) (52.4%–71.1%) 7 , 8 , 10 , 11 , 13 16 in women younger than 25 years, suggesting that treatment is often unnecessary. One UK study estimated that at most, 1.5% of young women treated for HSIL would have developed cancer by the age of 25 years, if left untreated, whereas more than half of them would have regressed by the age of 25 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 250 potentially eligible studies; 43 publications met the inclusion criteria (fig 1),6222324252627282930313233343536373839404142434445464748495051525354555657585960616263 but seven were duplicate reports of the same data 27283140505254. Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2). The median follow-up was 16 months (range 3-72, interquartile range 7.6-27.4 months).…”
Section: Resultsmentioning
confidence: 99%